Anthropology at the intersection of Medicine, Psychology and Culture - Strauss, D. F. M. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2004)
Developments within modern culture intimately cohere with advances within the domains of medicine and psychology. Medical technology penetrated into the secrets of the genetic code (the genome project) and increasingly assumes a guiding role in the life expecta ions of ordinary people, almost competing with the role of caring which 20th century psychology took over from the church. The desire to achieve medical control flowing from the modern spirit of technicism is placed against the back ground of the science-ideal. The reductionist consequences of the science-ideal are confronted with the alternative of a comprehensive totality perspective on the structure of being human. The latter is also protected against the relativistic implications entailed in the assessment of the uniqueness of cultures - by arguing that the latter does not contradict universal features, but presuppose them. The co-conditioning role of language is explained against the background of the so-called linguistic turn at the beginning of the 20th century. A brief discussion of the human subject in medical practices and within modern society is followed by the characterization of a fundamental circularity present in modern medicine.